Manual of model procedures and guidance notes for the implementation of the WTO Agreement on Technical Barriers to Trade (ITC GenevaCH, 2007)
Seeks to assist members of WTO to effectively exercise their membership rights with regard to the Technical Barriers to Trade (TBT) Agreement; to fulfill their obligations under the agreement; and, to facilitate trade by utilizing the mechanisms for the removal of unnecessary trade barriers that have become available as a consequence of the TBT Agreement.
Keywords: TRADE BARRIERS